Bank and sovereign risk pass‐through: Evidence from the euro area. (26th July 2019) - Erce, Aitor
Abstract: Sovereign and bank risk can feed into each other and trigger destabilizing dynamics. In this paper, I use euro‐area countries' credit default swap data to study what factors and shocks underlie bouts of enhanced correlation between bank and sovereign risk. Sovereign risk pass‐through, where sovereign instability undermines domestic banks' health, is stronger than bank risk pass‐through, where bank instability taints the sovereign's fiscal outlook. When banks are more exposed to the sovereign or the latter loses its investment‐grade status, sovereign risk transfers to banks particularly strongly. In the other direction, risk transmits to the sovereign from banks more strongly if the banks are larger or if the government is bailing them out. During bailout periods, bank risk pass‐through is more likely if banks hold more domestic sovereign debt, they are more externally indebted, or the sovereign debt stock is higher.